2023
DOI: 10.1029/2022ms003268
|View full text |Cite
|
Sign up to set email alerts
|

Data‐Driven Stochastic Lie Transport Modeling of the 2D Euler Equations

Abstract: A major challenge in geophysical and observational sciences is the representation and quantification of uncertainty in numerical predictions. Uncertainty stems from various sources, most relevantly from incomplete inclusion of all relevant physical mechanisms in the models and uncertainty in the initial and boundary conditions (T. N. Palmer, 2000). Important models for geophysical fluid dynamics, such as the two-dimensional Euler equations, quasi-geostrophic equations or rotating shallow water equations are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…Randomness is introduced via the term dB t lm in which B t lm is a general random process, defined for each pair l, m separately. The random process can be tailored to fit the measurement data [18], though the common choice is to let dB t lm be normally distributed with a variance depending on the time step size [29]. We choose the latter in what follows and include the variance scaling in σ lm .…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomness is introduced via the term dB t lm in which B t lm is a general random process, defined for each pair l, m separately. The random process can be tailored to fit the measurement data [18], though the common choice is to let dB t lm be normally distributed with a variance depending on the time step size [29]. We choose the latter in what follows and include the variance scaling in σ lm .…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…These approaches have also been applied successfully to more complete geophysical models. Examples include the modeling of uncertainty through Casimir-preserving stochastic forcing for the two-dimensional Euler equations [15,18,13] and energy-preserving stochastic forcing in the quasi-geostrophic equations [43]. An alternative approach is based on statistics of subgrid data that lead to a stochastic forcing and eddy viscosity, which has been applied to the barotropic vorticity equation on the sphere [20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is shown that a suitable model for large scales is given by the so called SALT equations [12], in which a transport noise term models the infinitesimal action of the small scales on the large ones. Several numerical tests have shown the usefulness of the SALT equations as a powerful tool for model reduction [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…(2021) and Ephrati et al. (2023) also implement stochastic forcing by exploiting the statistics from a high resolution reference case. In these studies, the full covariance matrix of the unresolved field is sampled, which is then represented using a truncated number of typically Empirical Orthogonal Functions (EOFs).…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach was applied to a multi-layer double gyre primitive equation simulation in Cooper (2017). Cotter et al (2020), Gugole and Franzke (2020), Brecht et al (2021) and Ephrati et al (2023) also implement stochastic forcing by exploiting the statistics from a high resolution reference case. In these studies, the full covariance matrix of the unresolved field is sampled, which is then represented using a truncated number of typically Empirical Orthogonal Functions (EOFs).…”
mentioning
confidence: 99%